Civil War minutes. Vol. 3, Gettysburg and stories of valor [videorecording (DVD)] - Bussler, Mark; Carradine, Keith, 1949- (Minutes of history series., 2004)
Keith Carradine narrates the third volume in the Civil War Minutes documentary series, Gettysburg and Stories of Valor. This two-disc box set presents a unique collection of 30 stories about people and artifacts from the Civil War. Disc One covers the Battle of Gettysburg with episodes such as: Colonel Strong Vincent's defense of Little Round Top; the "hallowed ground" of Gettysburg National Cemetery including the grave of President Nixon's great-grandfather; the mysterious Devil's Den photographs; General Winfield Scott Hancock's injury and presidential campaign;and Confederate General Lewis Armistead's secret distress call. Disc Two focuses on additional heroic and tragic moments in the Civil War such as: brutality at the Dead Line in Andersonville Prison; loss of charismatic Brigadier General Alexander Hays; medical and surgical history of the war; the Confederate President; and the explosion at Allegheny Arsenal. This documentary is a mixture of live footage from the battlefield, still pictures, drawings, engravings and never before seen photographs.